Inorganic Nanocrystals Functionalized Mesoporous Silica Nanoparticles: Fabrication and Enhanced Bio-applications - Zhao, Tiancong; Nguyen, Nam-Trung; Xie, Yang; Sun, Xiaofei; Li, Qin; Li, Xiaomin (Frontiers in Chemistry, 2017)
Mesoporous SiO2 nanoparticles (MSNs) are one of the most promising materials for bio-related applications due to advantages such as good biocompatibility, tunable mesopores and large pore volume. However, unlike the inorganic nanocrystals with abundant physical properties, MSNs alone lack functional features. Thus, they are not sufficiently suitable for bio-applications that require special functions. Consequently, MSNs are often functionalized by incorporating inorganic nanocrystals, which provide a wide range of intriguing properties. This review focuses on inorganic nanocrystals functionalized MSNs, both their fabrication and bio-applications. Some of the most utilized methods for coating mesoporous silica (mSiO2) on nanoparticles were summarized. Magnetic, fluorescence and photothermal inorganic nanocrystals functionalized MSNs were taken as examples to demonstrate the bio-applications. Furthermore, asymmetry of MSNs and their effects on functions were also highlighted.